Tathbîq Ayyâm al-Qawâ‘id fî Tarqiyat Fahm al-Qawâ‘id: تطبيق أيام القواعد في ترقية فهم القواعد - Aisyatul Hanun; Ulfi Samaratul Jinan; Amirul Mukminin (Cordova Journal, 2025)
Ayyamul Qawaid is one of the programs established by the management of the Central Arabic Language Dormitory. Ayyamul qawaid is the implementation of a program or rules that have been established with an agreement that has been planned to achieve the desired goal, namely what is meant here is that for three days (Monday, Tuesday and Wednesday) Arabic language boarding school students are required to speak using good qawaid and correctly by giving harakat for each end of the lafadz uttered when speaking, thus these three days are called ayyamul qawaid for female students at the Arabic Language Center girls' boarding school. This program aims to increase female students' understanding of qawaid lughawiyah, especially female students in the mutaqoddim class. Qawaid lughawiyah is an important element to master in language learning so that the language can be understood well and correctly by listeners and readers. In this research, the problem formulation is about: How is Ayyamul Qawaid implemented and how to increase the understanding of Qawaid? This approach and type of research uses descriptive qualitative methods, data collection uses observation, interviews and documentation techniques. The results of the research are: 1) The implementation of Ayyamul Qawaid in the Central Girls' Arabic Language Dormitory is enforced through strict control by the linguistics section of the boarding house administrators, where every Monday, Tuesday and Wednesday female students must speak with good and correct qaidah and are required to give the final meaning of each pronunciation. which is spoken. In its implementation, there is strict supervision of female students who violate the rules by not using correct and appropriate qawaid 2) Increased understanding of qawaid of Arabic language boarding female students, especially mutaqoddim classes, can be seen through tests carried out by qawaid teachers and language section administrators, female students have become accustomed to using the correct qawaid right when Ayyamul Qawaid takes place. The increase in students' understanding of qawaid can be seen from their daily speech, which is increasing in terms of the lugawi qaidah used when speaking.